2011
DOI: 10.1016/j.pain.2010.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance-based interventions for the treatment of chronic pain: A systematic review and meta-analysis

Abstract: Acceptance-based interventions such as mindfulness-based stress reduction program and acceptance and commitment therapy are alternative therapies for cognitive behavioral therapy for treating chronic pain patients. To assess the effects of acceptance-based interventions on patients with chronic pain, we conducted a systematic review and meta-analysis of controlled and noncontrolled studies reporting effects on mental and physical health of pain patients. All studies were rated for quality. Primary outcome meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
422
2
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 661 publications
(486 citation statements)
references
References 66 publications
29
422
2
8
Order By: Relevance
“…Development of strategies for identifying those at risk for nonadherence and boosting their engagement during and after the intervention may extend the potential benefits of MM practice to a larger group of patients. The perceived safety of MM-based interventions 18,19,27,49 was corroborated by this research. It is in stark contrast to opioid therapy, which has been linked to dose-dependent harms.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Development of strategies for identifying those at risk for nonadherence and boosting their engagement during and after the intervention may extend the potential benefits of MM practice to a larger group of patients. The perceived safety of MM-based interventions 18,19,27,49 was corroborated by this research. It is in stark contrast to opioid therapy, which has been linked to dose-dependent harms.…”
Section: Discussionsupporting
confidence: 73%
“…4 Although research on the efficacy of MM-based interventions for reducing pain is promising, existing evidence on MM's effects for pain and/or function in chronic noncancer pain is inconclusive and based on a limited number of rigorous RCTs. 27,34,35,49 In addition, there is an overall scarcity of research on long-term efficacy of therapeutic modalities, including MM and CBT, in opioid-treated populations. 5,18,19,27,34,35,49 Although MM modalities are overall considered feasible, acceptable, and safe, these aspects of MM interventions have not been well explored in, and evidence on their efficacy is insufficient for, opioid-treated CLBP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 A meta-analysis of "acceptance-based" treatment that included both ACT and mindfulness-based treatments concluded that these methods currently appear equally effective to standard CBT for chronic pain. 80 ACT is listed as an empirically supported treatment with "strong research support" for general chronic pain by the organization within the American Psychological Association that determines this. 73 Psychological Flexibility and Chronic Pain 22…”
Section: Psychological Flexibility Clarifies and Empowers Other Existmentioning
confidence: 99%
“…The effect size for such interventions is impressive (e.g., Haynes et al, 2008;Norton & Price, 2007;Olatunji, Cisler, & Deacon, 2010;OpriĹź et al, 2012). There are numerous examples of other multicomponent interventions developed without a preintervention functional assessment with documented effectiveness for problems including, but not limited to, depressive disorders (e.g., Cuijpers, Andersson, Donker, & van Straten, 2011;Hans & Hiller, 2013), pain management (e.g., Lunde, Nordhus, & Pallesen, 2009;Veehof, Oskam, Schreurs, & Bohlmeijer, 2011), and childhood conduct problems (Lee, Niew, Yang, Chen, & Lin, 2012;Maughan, Christiansen, Jenson, Olympia, & Clark, 2005). More often than not, these evidencebased interventions have an accompanying implementation manual.…”
Section: Recommendation 6: Consider Evidence-based Practices Beyond Fmentioning
confidence: 99%